The East German wage structure after transition - Orlowski, Robert; Riphahn, Regina Therese (Economics of Transition, 2009)
We extend the literature on transition economies’ wage structures by investigating the returns to tenure and experience. This study applies recent panel data and estimation approaches that control for hitherto neglected biases. We compare the life-cycle structure of East and West German wages for fulltime employed men in the private sector. The patterns in the returns to seniority are similar for the two regional labour markets. The returns to experience lag behind in the East German labour market, even almost 20 years after unification, with significant differences particularly for high-skill workers. The results are robust when only individuals who started their labour market career in the market economy are considered. We expect that the different returns are related to the heterogeneity of work experience gathered in East as compared with West German
WiSo-Import:2015-03-25:308
Keywords: Transformation